A CASE STUDY ON THE IMPACT OF INDUSTRIAL EFFLUENT DISPOSAL ON THE FISHERY OF AMBA RIVER ESTUARY, MAHARASHTRA - GAJBHIYE, S. N.; MEHTA, PRATIK; MUSTAFA, S.; NAIR, VIJAYALAKSHMI R. (Journal of Indian Fisheries Association, 2006)
The impact of waste discharge on fishery resources IS a n1.atter ofgreat concern. The accepted norm in all environmental impact assessmentstudies is to avoid areas of high fishery potential while locating a marineoutfall. Contemplating on this aspect a case study was conducted in theAmba River estuary before and after the establishment of a petrochemicalcomplex at Nagothane. The treated wastewater from this complex isreleased through a subsurface outfall after adopting effective controlmeasures for marine disposal of waste. Experimental trawling was doneat five locations covering a distance of 30 km during 1990 to 1991. Thecatch rate within the estuary varied from 0.6 to 255 kg/h (av 24 kg/h). Thetrend indicated considerable decrease in fishery potential from the mouthof the estuary (av 64 kg/h) to the upstream location (av 11 kg/h). A totalof 49 species of fishes, 16 species of prawns, 7 species of crabs and 1species of lobster were identified from the collections. Nu:mber of speciesgradually increased from the interior segment at Dharamtar (8) to theouter area near Revas (18). A comparison of the quantitative andqualitative nature of the post outfall and preoutfall data revealed onlymarginal difference. The study indicates that if necessary precautionsare taken to render the waste harmless the n1arine ecology will hardly beaffected.